2018
DOI: 10.1016/j.ijid.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal carriage in high-risk settings: A systematic review

Abstract: Preventative vaccination policies for high-risk groups should be based on current disease data in individual countries, supplemented by carriage data. Meningococcal carriage studies and disease surveillance are critical for determining the local epidemiology, populations responsible for disease transmission, and the need for targeted vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
1
37
1
1
Order By: Relevance
“…84,85 Since the inclusion of the quadrivalent meningococcal vaccine in 2001, 85 no major meningo coccal meningitis outbreaks related to hajj have been identified. [85][86][87] However, concern that new serogroups of N meningitidis (eg, B and X), which are not covered in the current quadrivalent vaccine targeting serogroups A, C, W135, and Y, could be a cause of future epidemics is increasing. 88,89 Owing to the high incidence of pertussis seen among Hajj pilgrims in 2003, 90 Bordetella pertussis is considered a risk in pilgrims, especially those who have not completed their immuni sation schedule.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…84,85 Since the inclusion of the quadrivalent meningococcal vaccine in 2001, 85 no major meningo coccal meningitis outbreaks related to hajj have been identified. [85][86][87] However, concern that new serogroups of N meningitidis (eg, B and X), which are not covered in the current quadrivalent vaccine targeting serogroups A, C, W135, and Y, could be a cause of future epidemics is increasing. 88,89 Owing to the high incidence of pertussis seen among Hajj pilgrims in 2003, 90 Bordetella pertussis is considered a risk in pilgrims, especially those who have not completed their immuni sation schedule.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…Conjugate vaccines are more effective in controlling the carriage of meningococci [29,30] but are considerably more expensive. Meningococcal serogroups that are not covered by the current quadrivalent vaccine were frequently isolated from throat swabs collected from pilgrims, namely, serogroups B and, less frequently, X [31][32][33]. A recent systematic review concluded that serogroup B dominated the carriage acquisition among Hajj pilgrims [32], and most carriers received the polysaccharide vaccine, which is not expected to reduce the carriage acquisition of serogroups contained in the vaccine [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Meningococcal serogroups that are not covered by the current quadrivalent vaccine were frequently isolated from throat swabs collected from pilgrims, namely, serogroups B and, less frequently, X [31][32][33]. A recent systematic review concluded that serogroup B dominated the carriage acquisition among Hajj pilgrims [32], and most carriers received the polysaccharide vaccine, which is not expected to reduce the carriage acquisition of serogroups contained in the vaccine [34,35]. The opportunity to prevent future outbreaks depends on an ongoing review of the current mandatory vaccination policy in view of these and future developments.…”
Section: Discussionmentioning
confidence: 99%
“…The highest carriage prevalence has been reported in populations in semiclosed settings or with extensive close contact, such as universities (6)(7)(8) and military barracks (9,10). Studies have shown that meningococcal carriage is highly dynamic and may be chronic, intermittent, or transient (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%